Bird predation on nest of a social wasp in Brazilian cerrado - Barros Henriques, Raimundo Paulo; Torre Palma, Alexandre Ramlo (Revista de Biología Tropical, 1998)
Birds are rarely observed preying upon wasps' nests (Bertoni 1911, Rau 1941, AIvarez del Toro 1950, Skutch 1959, Windsor 1976). Many of the observations are recorded in tropical forest on nests of Polybia and Metapolybia. In this note we present the first observations on the predation by the curIcrestedjay (Cyanocorax cristatellus) upon the nest of a social wasp (Apoica pallens) in cerrados of Central Brazil.